1974
DOI: 10.1111/j.1365-2184.1974.tb00405.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Adrenoreceptor Activity on Crypt Cell Proliferation in the Rat Jejunum

Abstract: The influence of adrenergic stimulation, adrenergic blockade and sympathectomy on crypt cell cycle time and mitotic time in rat jejunum was studied. Alpha adrenergic stimulation by noradrenaline was found to shorten both cell cycle and mitotic times, whereas beta adrenergic stimulation by adrenaline or isoprenaline was found to prolong both cell cycle and mitotic times. Conversely, alpha adrenergic blockade by phentolamine prolonged cell cycle time and beta adrenergic blockade by propranolol or practolol short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
61
3
2

Year Published

1979
1979
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 29 publications
3
61
3
2
Order By: Relevance
“…It is not possible from the present experiments to determine whether the PG analogues are acting directly on the proliferating cells or indirectly through, for example, changes in blood supply, intestinal motility or mastcell activity. PG F2, has been shown to act, in some cases at least, by raising intracellular levels of cyclic guanosine monophosphate (cGMP) (Kuehl et al, 1973) and 3 other agents that have been shown to stimulate the formation of cGMP, namely noradrenaline (Schultz et al, 1975), acetylcholine (Goldberg et al, 1973) and serotonin (Goldberg et al, 1974), as well as dibutyryl cGMP itself, have been shown to accelerate jejunal-crypt cell proliferation (Tutton & Helme, 1974;Tutton, 1974Tutton, , 1977Tutton & Barkla, 1979b). However, in the case of colonic adenocarcinoma, whilst both serotonin (Tutton & Barkla, 1978b) and dibutyryl cGMP (Tutton & Barkla, 1979b) promote cell division, the PG F2, analogue inhibits both cell division and xenograft growth.…”
Section: Mitotic Rate In Ratmentioning
confidence: 99%
See 3 more Smart Citations
“…It is not possible from the present experiments to determine whether the PG analogues are acting directly on the proliferating cells or indirectly through, for example, changes in blood supply, intestinal motility or mastcell activity. PG F2, has been shown to act, in some cases at least, by raising intracellular levels of cyclic guanosine monophosphate (cGMP) (Kuehl et al, 1973) and 3 other agents that have been shown to stimulate the formation of cGMP, namely noradrenaline (Schultz et al, 1975), acetylcholine (Goldberg et al, 1973) and serotonin (Goldberg et al, 1974), as well as dibutyryl cGMP itself, have been shown to accelerate jejunal-crypt cell proliferation (Tutton & Helme, 1974;Tutton, 1974Tutton, , 1977Tutton & Barkla, 1979b). However, in the case of colonic adenocarcinoma, whilst both serotonin (Tutton & Barkla, 1978b) and dibutyryl cGMP (Tutton & Barkla, 1979b) promote cell division, the PG F2, analogue inhibits both cell division and xenograft growth.…”
Section: Mitotic Rate In Ratmentioning
confidence: 99%
“…However, the response to a particular agent varies markedly between each of the tissues examined. For example, o-adrenoceptor agonists promote cell division in the jejunal and colonic epithelium but not in colonic adenocarcinomas (Tutton & Helme, 1974;Tutton & Barkla, 1977), whereas histamine and serotonin promote cell division in the jejunal crypts (Tutton, 1974 and in colonic tumours, but not in colonic crypts (Tutton & Barkla, 1978a, b). The (Druckrey et al, 1967;Tutton & Barkla, 1976).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…IT IS NOW well recognized that biogenic amines are able to exert short-term influences, both excitatory and inhibiting, on cell proliferation in various malignant and non-malignant tissues (Bullough & Laurence, 1966;Byron, 1972Byron, , 1977Epifanova & Tchoumak, 1963;Hadden et al, 1970;Hunt & Tutton, 1976;Klein, 1977;Leeson & Voaden, 1970, Norrby, 1973Tutton, 1974Tutton, , 1976Tutton & Barkla, 1976, 1978aTutton & Helme, 1974). However, the influence of these ubiquitous agents on cell proliferation in human tumours and on volumetric changes in neoplasms does not appear to have been reported.…”
mentioning
confidence: 99%